The Impacts of Time of Birth on Maternal and Perinatal Outcomes in Low-Risk Pregnancy in Khartoum, Sudan: A Cross-Sectional Hospital-Based Study - Eltayeb, Ayia (International Journal of Innovative Research in Medical Science, 2023)
Background: The literature shows inconsistency about the influencing of time of birth on pregnancy outcomes across countries, no such data exit in Sudan. Thus, the current study aimed to investigate the influence of time and day of birth on maternal and perinatal outcomes among women with low-risk pregnancy in Khartoum, Sudan. Methods: A cross-sectional study was conducted from July 2021 to August 2022 in Saad Abuelela maternity hospital, Khartoum Sudan. A structured questionnaire was used to collected sociodemographic and obstetrical data. Chi-square test was performed. Results: A total of 388 pregnant women were recruited from all low-risk women who delivered in the hospitals The mean (standard deviation) age of the women was 28.26(6.9) years and 172 (44.3%) were primiparas. According to type/frequency of complications occurred, those who were shifted to interventional delivery for fetal compromise 162(41.8%) i.e. emergency caesarean delivery 139(35.8%), and instrumental delivery 23 (5.9%); total maternal complications 51(13.1%) including who 3rd or 4th perineal tears were 12(3.1%), who complicated by postpartum hemorrhage were 36(9.3%), who experienced uterine rupture were 3(0.8%); total neonatal complications 175(45.1%) i.e. who had newborn birth injuries were 10(2.6%); who had birth Asphyxia were 62(16.0%) and who had neonatal admission to neonatal intensive care unit (NICU) were 103(26.5%). There was no association between type/frequency of complications and part of the week (working days vs. weekend days) (P value = 0.915), there was a significant statistical association with part of the day (daytime vs. evening and night-time) (P value = 0.005). Conclusion: Poor maternal and perinatal outcomes among low risk Sudanese pregnant women was found to be associated with time per day regardless of week or weekend day and not day of week. All efforts should be directed to provide appropriate healthcare services for all pregnant women regardless of time, assessing our local healthcare systems (its weakness, strengths, and opportunities) is a good start to improve maternal and perinatal health in Sudan.